1992
DOI: 10.1017/s0305004100075587
|View full text |Cite
|
Sign up to set email alerts
|

Generalized maximal surfaces in Lorentz–Minkowski space L3

Abstract: In this paper we carry out a systematic study of generalized maximal surfaces in Lorentz–Minkowski space L3, with emphasis on their branch points. Roughly speaking, such a surface is given by a conformal mapping from a Riemann surface S in L3. In the last years, several authors [1, 2, 5, 6] have dealt with regular maximal surfaces in L3, i.e. with isometric immersions, with zero mean curvature, of Riemannian 2-manifolds M in L3. So, the term ‘regular’ means free of branch points. As in the minimal case, a conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 6 publications
1
72
0
Order By: Relevance
“…Definition 2.1 ( [7]). Let S be a Riemann surface and y = (x, y, t) : S → L 3 be nonconstant and harmonic.…”
Section: Generalized Spacelike Maximal Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 2.1 ( [7]). Let S be a Riemann surface and y = (x, y, t) : S → L 3 be nonconstant and harmonic.…”
Section: Generalized Spacelike Maximal Surfacesmentioning
confidence: 99%
“…In [7] it is introduced as the unique, up to homothety and translation, spacelike maximal surface in L 3 which is the graph of a function of the form t = f (x) + g(y). Being spacelike, the graph is considered only over the region {(x, y) : tanh 2 x + tanh 2 y < 1}.…”
Section: Introductionmentioning
confidence: 99%
“…If D is an open disc and X : D → ‫ތ‬ 3 is a maximal immersion with a spacelike singular point in q ∈ D, the local behavior at the singularity is similar to the case of minimal surfaces in ‫ޒ‬ 3 (see [Dierkes et al 1992;Estudillo and Romero 1992;Fernández et al 2005]): X is not a topological embedding, D−{q} with the induced metric is conformally equivalent to {z ∈ ‫ރ‬ | 0 < |z| < 1}, the Weierstrass data (g, 3 )…”
Section: Preliminariesmentioning
confidence: 99%
“…In this line, Bartnik and Simon [1982/83] obtained results on the existence and regularity of spacelike solutions to the boundary value problem for the mean curvature operator in ‫ތ‬ n+1 , and Kobayashi [1984] investigated surfaces with conelike singularities. Estudillo and Romero [1992] defined a class of maximal surfaces with singularities of other types and studied criteria for such a surface to be a plane. On the other hand, Klyachin and Mikyukov [1993] have tackled the problem of existence of solutions to the maximal hypersurface equation in ‫ތ‬ n+1 with prescribed boundary conditions and a finite number of singularities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in contrast to the case of minimal surfaces in E 3 , motivated by Calabi's work [1], Cheng and Yau [2] showed that the only complete maximal surfaces are spacelike planes. From this fact, more general classes of maximal surfaces with singularities such as maxfaces in [22] or generalized maximal surfaces in [3] have been frequently studied. Similarly, timelike minimal surfaces with singularities have been studied and many examples constructed.…”
Section: Introductionmentioning
confidence: 99%